Identifying Key Drivers of Repurchase Intentions for Sari Roti Products Using Binary Logistic Regression Analysis - Annisa Liestiani; Ayu Wulandari; E. N. Budiyanto Hariandja; Jerry Heikal (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze various factors that influence the repurchase decision of Sari Roti products. The method used in this research is binary logistic regression using the SPSS tool. A sample of 156 consumers was randomly selected. Data was collected through a survey filled out by 156 Sari Roti consumers. The survey results were entered into Microsoft Excel and then normalized. For Independent Variable and Dependent Variable data in the form of text